The Diagnosis and Management of Desmoplastic Ameloblastoma of the Maxilla A Case Report on Partial Maxillectomy with Obturator Fixation - .S, Rakkeshpraveen; Avinash.J, Sai; Dheenadhayalan, M.; Karthickeyan, K.; Shanmugasundaram, P.; Sri, M. K. Sundar (Journal of Neonatal Surgery, 2025)
Desmoplastic ameloblastoma (DA) is a rare, benign, but locally aggressive variant of ameloblastoma, a tumor that typically affects the jaw and arises from odontogenic epithelium. DA is characterized by a dense fibrous stroma and is most commonly found in the mandible, although its occurrence in the maxilla is rare. This case report presents our experience with desmoplastic ameloblastoma in the maxilla, focusing on its clinical, diagnostic, and therapeutic features. The chief complaint was a slowly progressive painless swelling in the right maxillary region, which had been gradually increasing in size over the past 3 years. The medical history was non-contributory with no significant family history. Extraoral examination of the face revealed no facial asymmetry, swelling, or midline bony hard swelling in the face. On intraoral examination, there was a non-tender, immovable swelling. There was no evidence of suppuration or pus discharge. The swelling caused mild dysphagia (difficulty in chewing) and dysarthria (difficulty in pronunciation). Investigations confirmed the diagnosis of desmoplastic ameloblastoma. A CT scan showed an expansile lytic lesion involving the maxilla, and histopathological analysis of the excised lesion indicated a benign clinical course. The patient underwent right partial maxillectomy with obturator fixation, which involved excising the tumor and adjacent structures. The maxillary defect was reconstructed with prosthetic rehabilitation of the maxillary arch. The patient experienced good functional recovery, with improvements in speech and chewing, and there was no evidence of tumor recurrence on follow-up. The patient was satisfied with both the functional and aesthetic outcomes of the procedure